1992
DOI: 10.2169/internalmedicine.31.1128
|View full text |Cite
|
Sign up to set email alerts
|

Wegener's Granulomatosis in a Patient with a Rheumatoid Arthritis.

Abstract: A 38-year-old woman with rheumatoid arthritis who developed Wegener's granulomatosis is described. Wegener's granulomatosis appeared with saddle nose, perforation in her nasal septum, and granuloma in the nasal cavity. Laboratory evaluation showed a positive rheumatoid factor and circulating immune complex. Radiographic examination revealed ankylotic changes in both wrist and elbow joints. Bilateral anosmia and other disease manifestations completely responded to treatment with oral cyclophosphamide and predni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…RA has been rarely reported to be associated with WG (7)(8)(9). In the present case, the long-standing disease duration and the characteristic symmetrical deformities of multiple small joints of the extremities confirmed the coexistence of RA and excluded the possibility of prodromal symptoms for WG from long-lasting polyarthralgia and elevated RF.…”
Section: Discussionmentioning
confidence: 99%
“…RA has been rarely reported to be associated with WG (7)(8)(9). In the present case, the long-standing disease duration and the characteristic symmetrical deformities of multiple small joints of the extremities confirmed the coexistence of RA and excluded the possibility of prodromal symptoms for WG from long-lasting polyarthralgia and elevated RF.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study which focussed on chemosensory function in WG patients. Two previous case reports [14,15] and one large series on cranial nerve involvement in Wegener disease mention anecdotally chemosensory symptoms without having measured and them [16]. Recently, Laudien et al [17] also screened WG patients for olfactory identification suggesting that up to 18% of them had lowered olfactory identification scores.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of WG complicated by typical RA have been reported (12,13). Polyarthralgia is a relatively common symptom in WG patients, but arthritis is transient and non-destructive (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…As the etiology of WG is still unknown, the pathogenesis of overlapping diseases is obscure. Ohashi et al (12), however, suggested that a common etiological factor implicated the production of an immune complex in a case of overlapping RA and WG.…”
Section: Discussionmentioning
confidence: 99%